Inside Cover: Natural Abundance 17O DNP NMR Provides Precise O−H Distances and Insights into the Brønsted Acidity of Heterogeneous Catalysts (Angew. Chem. Int. Ed. 31/2017). Issue 31 (9th June 2017) - Perras, Frédéric A.; Wang, Zhuoran; Naik, Pranjali; Slowing, Igor I.; Pruski, Marek
Abstract : Brønsted acidic sites on catalyst surfaces are observed by 17 O dynamic nuclear‐polarization‐enhanced NMR spectroscopy, which hyperpolarizes nuclei by microwave‐induced saturation of electrons. In their Communication onpage 9165 ff., M. Pruski et al. report the measurement of O−H distances with sub‐picometer precision. The length of the O−H bond is directly related to the Brønsted acidity of the sites and is also a reporter of the formation of intermolecular hydrogen‐bonding interactions.